Development of a Middleware between SUMO simulation tool and JaCaMo framework - Van Haare Heijmeijer, Alexis; Vaz Alves, Gleifer (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2018)
Smart City has an infrastructure that works with technology to reduce daily problems. The lack of parking spots is one of these problems that can be controlled by creating Smart Parking systems. The MAPS (Multi-Agent Parking System) project studies and develops multi-agent systems for smart parking using JaCaMo framework to implement agents and artifacts. This paper presents the so-called MAPS-SUMO, a middleware between the MAPS project and SUMO, a simulation tool used for urban traffic. Our middleware allows a graphical representation for the simulation executed by MAPS agents.